Pengaruh El Nino-Southern Oscillation (ENSO) dan Madden-Julian Oscillation (MJO) Terhadap FREKUENsi Siklon Tropis di Indonesia Pada Periode Angin Monsun Baratan - samoria, yakubos (Jurnal Widya Climago, 2024)
Tropical cyclones have occurred frequently in the Indonesian region and its vicinity, where these tropical cyclones have significant impacts on the atmospheric conditions in the traversed areas. Tropical cyclones have occurred prominently in the Indonesian region, especially during the western monsoon period. The El Niño-Southern Oscillation (ENSO) and Madden-Julian Oscillation (MJO) are factors that modulate tropical cyclones. Not all tropical cyclones occurring during the western monsoon period are accompanied by the same ENSO and MJO periods. Therefore, this study aims to determine the extent to which the presence of ENSO and MJO influences the existence of tropical cyclones during the western monsoon period in the Indonesian region. Based on tropical cyclone data from 1989 to 2018, there have been a total of 363 tropical cyclone occurrences within the research boundaries of 900 E to 1600 E and 200 N to 200 S. Of these, 169 events occurred in the southern hemisphere (SH) and 194 events in the northern hemisphere (NH). The grouping of tropical cyclones was conducted as a method to understand the extent of tropical cyclone existence influenced by the presence of ENSO and MJO during their occurrence. The results of this study indicate that tropical cyclones in the NH region of Indonesia are more likely to occur during ENSO periods (El Niño and La Niña) when MJO is concurrently active, compared to periods when ENSO occurs without active MJO. In contrast, in the SH region of Indonesia, tropical cyclones are more dominant when La Niña phenomena coincide with each MJO period compared to periods when El Niño coincides with each MJO period.